# The Factor Theorem. Using The Factor Theorem Method To Prove That A Polynomial Has A Root.

The factor theorem can be used to locate the roots of a polynomial. The roots are where the polynomial crosses the x-axis. The factor theorem states that:

**If (x- a) is a factor of f(x) then f(x) = 0 or if f(ax-b) is a factor of f(x) the f(b/a) = 0**

Let’s put this factor theorem into practice:

**Example 1**

Show that x-3 is a factor of f(x) = x² - x – 6.

First make x -3 = 0 and solve this equation to give x = 3.

So all you need to do now is work out the value of f(3).

f(3) = 3² - 3 -6 = 9 – 3 -6 = 0

So by the factor theorem then x – 3 is a factor of f(x)

**Example 2**

Show that x+2 is a factor of f(x) = x² - 3x – 10.

First make x + 2 = 0 and solve this equation to give x = -2.

So all you need to do now is work out the value of f(-2).

f(3) = (-2)² - 3×(-2) -10 = 4 + 6 – 10 = 0

So by the factor theorem then x + 2 is a factor of f(x).

**Example 3**

Show that x-7 is a factor of f(x) = x² - 8x +7.

First make x - 7 = 0 and solve this equation to give x = 7.

So all you need to do now is work out the value of f(7).

f(7) = (7)² - 8×(7) +7 = 49 – 56 + 7 = 0

So by the factor theorem then x - 7 is a factor of f(x)

The next two examples are a little bit harder

**Example 4**

Show that 3x-2 is a factor of f(x) = 3x² + 10x – 8.

First make 3x - 2 = 0 and solve this equation to give x = 2/3

So all you need to do now is substitute f(2/3):

f(2/3) = 3(2/3)² + 10×(2/3) -8 = 12/9 + 20/3 – 8 = 12/9 + 60/9 – 72/9 = 0

So by the factor theorem then 3x - 2 is a factor of f(x).

**Example 5**

Show that x – 1 is a factor of f(x) = x³ + 2x² -x -2 = 0

First make x – 1 = 0, so the value of x we need is x = 1.

So substitute f(1) into this cubic equation:

f(1) = 1³ + 2×1² - 1 -2 = 1 + 2 -1 -2 = 0.

Therefore by the factor theorem, x -1 is a factor of f(x).

So as you can see the factor theorem is quite easy to carry out. All you need to do is set the factor equal to 0, solve this equation and then substitute this value into f(x) which should give you 0.

The factor theorem can be used to help you factorise fully harder polynomials.

## More by this Author

- 0
The surface area of a triangular prism can be found in the same way as any other type of prism. All you need to do is calculate the total area of all of the faces. A triangular prism has 5 faces, 3 being rectangular and...

- 0
The density, mass and volume triangle is as follows: So if you wanted to work out the density, you would cover up density in the magic triangle to give: Density = Mass/Volume (since mass is above volume) So if...

- 26
A compound shape is a shape that is made up from other simple shapes. In this article we will be working out the area of a L shape (made up from 2 rectangles). To find the area of a compound shape, follow these simple...

## Comments

No comments yet.